Condition Rating System For Thailand’s Concrete Bridges - Suksuwan, Nukul; Hadikusumo, Bonaventure H.W. (Penerbit Universiti Sains Malaysia, 2010)
The Bridge Management System (BMS) is designed to maximise use of available data and determine the optimal strategy to perform necessary improvements to bridges in the most cost-effective manner. This paper provides a condition rating system to meet the requirements of Thailand’s Department of Highways (DOH). A rating system to assess the existing condition of bridges is proposed. Segmental inspection is developed to execute efficient elementlevel evaluations and collect data that demonstrate deterioration patterns in bridge elements. The paper also describes inspection procedures for field survey execution, which enables observed distresses at the level of sub-elements or members to be allocated. Recommendations from bridge experts reveal that the proposed rating system is robust, implementable in actual practice, and suitable for efficient application in evaluating the nation’s concrete highway bridges. Although the bridge condition rating was developed in response to the specific characteristics of Thailand’s bridges, the proposed methodology can easily be extended to other bridge agencies.